ANALISIS PERBANDINGAN KINERJA KEUANGAN PT TELKOM INDONESIA (PERSERO) TBK DAN PT INDOSAT TBK TAHUN 2022-2024 - Ni Luh Eka Lestari; Ni Nyoman Suli Asmara Yanti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: Financial performance is a crucial indicator for assessing a company’s health and prospects, particularly in the rapidly growing telecommunications sector amid digital transformation. The purpose of this study is to compare the financial performance of two telecommunications companies to assess their effectiveness in financial management and competitiveness.Methods: “This study uses a descriptive quantitative method using financial report data for the 2022–2024 period obtained from the Indonesia Stock Exchange (IDX). The analysis was conducted using financial ratios, including liquidity ratios (current ratio, quick ratio, cash ratio), solvency ratios (DAR, DER), activity ratios (TATO, FATO), and profitability ratios (NPM, ROE, ROI)”Results: The study shows higher liquidity, capital structure, asset utilization efficiency, and profitability than Indosat. The liquidity and solvency are relatively stable, with better asset efficiency and superior profit-generating capabilities from equity and total assets. Conversely, Indosat shows an improving trend in several ratios, but its value remains below Telkom's. These findings provide a proportional financial comparison between state-owned companies and large private operators, and serve as a reference for strategic decision-making in the telecommunications sector. Keywords: Activity, Liquidity, Profitability, Solvency